ANALISIS KEPUASAN PENGUNJUNG EKOWISATA KABUPATEN MALANG - Boedirachminarni, Arfida; Suliswanto, Muhammad Sri Wahyudi (Jurnal Ekonomi Pembangunan, 2017)
This study aims to identify the factors that affect the satisfaction of ecotourism visitors Malang regency. The analytical tool used is to identify the factors that influence ecotourism performance using multiple regression analysis. The results of the analysis can be obtained the following conclusions: First, the influence of entertainment and supporting facilities are not significant indicate that the two variables are not the main determinant of visitor satisfaction as a representation of ecotourism performance. However, services and natural conditions are significantly more influential on ecotourism performance in Malang Regency. Secondly, the success of ecotourism is determined by management management as the result of analysis shows that service is the dominant variable in influencing visitor's satisfaction, so it needs synergy from all parties including government policy.